\(a-b=\frac{a}{b}\)
\(\Rightarrow\frac{a}{b}-a+b=0\)
\(a.\left(\frac{1}{b}-1\right)-b.\left(\frac{1}{b}-1\right)=-1\)
\(\left(a-b\right).\left(\frac{1}{b}-1\right)=-1\)
=>\(\left(a-b\right).\left(\frac{1}{b}-1\right)=\left\{\pm1\right\}\)
\(\hept{\begin{cases}a-b=1\\\frac{1}{b}-1=-1\end{cases}hay}\hept{\begin{cases}a-b=-1\\\frac{1}{b}-1=1\end{cases}\Rightarrow\hept{\begin{cases}KTM\\\frac{1}{b}=0\left(KTM\right)\end{cases}}}hay\hept{\begin{cases}a=-\frac{1}{2}\\b=\frac{1}{2}\end{cases}}\)
vì a,b là số tự nhiên => ko có giá trị nào thỏa mãn